Generation of Induced Pluripotent Stem Cells from Human Amniotic Fluid Cells by Reprogramming with Two Factors in Feeder-free Conditions - LI, Qing; FAN, Yong; SUN, Xiaofang; YU, Yanhong (Journal of Reproduction and Development, 2013)
The ectopic expression of transcription factors for reprogramming human somatic cells to a pluripotent state represents a valuable resource for the development of in vitro-based models for human disease and has great potential in regenerative therapies. However, the majority of studies have used skin fibroblasts to generate induced pluripotent stem cells (iPSCs) that typically require the enforced expression of several transcription factors, thereby posing a mutagenesis risk by the insertion of viral transgenes. To reduce this risk, iPSCs have been generated with OCT4 and KLF4 from human neural stem cells that endogenously express the remaining reprogramming factors. However, human neural stem cells are rare and difficult to obtain. Here, we show that iPSCs can be generated from human amniotic fluid cells (hAFCs) with two transcription factors: OCT4 and KLF4. Furthermore, iPSCs can be readily derived from hAFCs in a feeder-free conditions, thereby eliminating the potential variability caused by using feeder cells. Our results indicate that hAFCs represent an accessible source of cells that can be reprogrammed into pluripotent stem cells with two Yamanaka factors. Therefore, hAFCs may become a preferred cell type in the future for safe reprogramming without any exogenous genetic material.